Using Web Camera Enet to Measure Statistical Characteristic of Homogenous Target Illuminated by Different Tungsten Light - Abed Muslim, S. H.; Abass, H. K.; Al-Zuky, A. A.D. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of White Place Image ( Test Image ) A4 has been studied as a function of luminous intensity using the t tu un ng gs st te en n l la am mpp and web camera enet. It was found that the tungsten lamp gives almost even intensities for the three color band and lighting composite at low voltage .while at high voltage causes a fare from each other . The statistical characteristic(mean and stander deviation ) results for three colors composites RGB and lighting composites L showed that the mean and stander deviation increases with the increase of voltage possibly owing to the increase image resolution, which reflects the value of stander deviation for the blue band greater than red ,green bands and lighting composites because of the high contribution of noise in it.